(untitled) (مجلة إحالات, 2026)
This research explores the literary dimensions of Abdelhamid Ben Badis’s thought and his role in the Algerian cultural renaissance. It focuses on his prose and poetry—particularly his articles and speeches—highlighting their artistic value and his mastery of Arabic rhetorical techniques. The study emphasizes his use of Islamic heritage and eloquent language to address national issues and liberate Algerian youth from the superstitions and heresies promoted by colonial powers. It also examines his pivotal role in founding the Association of Algerian Muslim Scholars on authentic Islamic foundations. His writings reflect the essence of the reform movement and stand as a form of intellectual resistance to colonialism.